Lepton universality violation by Kaluza-Klein neutrinos in b → sll transition - Janus Capellan Aban (Physics Letters B, 2022)
Recent measure of RK, involving the decays of b→sl+l−, by the LHCb at CERN strengthened the deviation from the Standard Model prediction. The best fit in the updated global analysis suggests that the muon specific Wilson coefficients C9bsμμ=−C10bsμμ should be about −0.41. In this paper, we show that the accumulate effects of KK modes of a singlet Dirac neutrino propagating in the large extra-dimensional space naturally provide C9bsll=−C10bsll to explain the anomaly. By taking the muon Yukawa coupling to be about 5, the fundamental scale in the extra-dimensional framework should be lowered down to about 20 TeV if there are two additional spatial dimensions.